BUILDING PILLARS OF BUREAUCRATIC REFORM: THE STUDY OF IMPLEMENTATION OF INTEGRITY ZONE POLICY IN GORONTALO - Jurni Biahimo; Sastro Mustapa Wantu, Yanti Aneta, Ismet Sulila (Adisam Publisher, 2025)
This study aims to analyze the implementation of bureaucratic reform policies in Gorontalo Province, with a focus on the development of integrity zones towards Corruption-Free and Clean and Serving Bureaucratic Areas. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and studies documentation. The results of the study indicate that the implementation of bureaucratic reform policies in Gorontalo has had a positive impact, such as improving the quality of public services, The efficiency, and strengthening the accountability of the apparatus. However, there are significant obstacles, including resistance to change, budget constraints, and lack of coordination between work units. On the other hand, support from regional leaders, commitment of the apparatus, and the existence of clear technical guidelines are supporting factors in the implementation of this policy. The recommended strategies are strengthening the capacity of implementers, decentralizing decision-making, digitalizing public services, intensive socialization to the community, and data-based policy evaluation. With the implementation of this strategy, it is hoped that bureaucratic reform in Gorontalo can run more effectively, producing a bureaucracy that is professional, transparent, and responsive to the needs of the community.